2018
DOI: 10.1007/s00216-018-1227-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-assisted biotinylated single-chain variable fragment antibody-based immunoassay for amantadine detection in chicken

Abstract: A sensitive competitive immunoassay with simple operation was developed for the detection of the anti-virus drug amantadine (AMD). The single-chain variable fragment (scFv) antibody against AMD was site-specific biotinylated and overexpressed as a secreted body in Escherichia coli AVB101. Horseradish peroxidase-labeled streptavidin-biotinylated scFv antibody (HRP-SA-BIO-scFv) could specifically bind to AMD-functionalized magnetic beads (MBs) and then the immune complexes were separated from the matrix solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is often difficult to obtain scFvs that can maintain the same specificity as the maternal mAbs. Some previous articles reported that scFv antibodies showed similar or better performances than that of the parental mAbs ( Wen et al, 2012 ), but other articles reported that scFv antibodies performed worse than the parental mAbs ( Xie et al, 2018 ). Min et al amplified the anti-FB 1 single-stranded antibody gene on the basis of anti-FB 1 hybridoma cells and converted it to E. coli to obtain anti-FB 1 single-stranded antibody with the an IC 50 reducing 12 times approximately 2000 ng/ml compared with the original mAb ( Min et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is often difficult to obtain scFvs that can maintain the same specificity as the maternal mAbs. Some previous articles reported that scFv antibodies showed similar or better performances than that of the parental mAbs ( Wen et al, 2012 ), but other articles reported that scFv antibodies performed worse than the parental mAbs ( Xie et al, 2018 ). Min et al amplified the anti-FB 1 single-stranded antibody gene on the basis of anti-FB 1 hybridoma cells and converted it to E. coli to obtain anti-FB 1 single-stranded antibody with the an IC 50 reducing 12 times approximately 2000 ng/ml compared with the original mAb ( Min et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…IMBs can quickly separate samples from the matrix, preserve the biological activity and integrity of samples, and reduce the complex pretreatment steps in the instrument detection method, thereby improving the detection efficiency. In 2018, Xie et al 42 established a highly sensitive ELISA assay based on MB and BAS based on biotinylated scFv and measured an IC 50 of 1.93 ng/mL for amantadine for actual chicken meat sample detection. Enzyme-catalyzed biotin-labeled scFv can only be linked by one biotin to one scFv and cannot amplify the signal well; therefore, in this study, chemobiotin-labeled RAC-scFv was used and directly conjugated with streptavidin beads, and the selected bead size was 1 μm, which has good dispersion stability and facilitates the detection of small molecules.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Wang et al, 2010), fluoroquinolones (Tao et al, 2013;Wang, Dong, et al, 2016;Wen et al, 2012), β-lactams (X. He et al, 2017;He, Wei, et al, 2019;Liu, Zhang, et al, 2016), and others (Dong et al, 2021;Li, Hou, et al, 2021;Xie et al, 2018) (Table 3).…”
Section: Veterinary Drug Residuesmentioning
confidence: 99%
“…In recent years, with the support of phage display that provides a powerful tool for the development of scFvs in veterinary drug immunoassays, scFvs against a variety of veterinary drugs have been screened, including β‐agonists (J. X. Dong et al., 2012; Dong, Xie, et al., 2014; Lee et al., 2018; Lu et al., 2020; H. Wang et al., 2010), fluoroquinolones (Tao et al., 2013; Wang, Dong, et al., 2016; Wen et al., 2012), β‐lactams (X. He et al., 2017; He, Wei, et al., 2019; Liu, Zhang, et al., 2016), and others (Dong et al., 2021; C. Li et al., 2016; Li, Hou, et al., 2021; Xie et al., 2018) (Table 3).…”
Section: Application Prospects Of Scfvs In Food Safetymentioning
confidence: 99%